Process safety accident analysis in process chemical industries / Muhammad F. Husin - Husin, Muhammad F.; Mohamad, Ahmad Aizuddin; Ahmad Zukeri, Nur Akma; Ahmad Nizam, Anis Shahirah; Zamri, Mirza Qaddriena
Process safety accident analysis is through investigation of incidents to identify the chain of events and causes so that corrective measures can be developed and implemented in order to reduce the consequences of future similar incidents. Leveraged strategies that minimise the occurrence of entire types of accidents can be created by recognising and resolving the root causes of equipment failures and personnel errors. In this era of development, many chemical industries are run around the world but for this safety accident analysis only focused on refinery, petrochemical plant, gas processing plant and the upstream within 1998 until 2018. This industry is in very high demand to make a chemical-based product and it also produces products from those chemicals via domestically and to the worldwide. But there are many accidents that occur that lead to the both large and small losses in the process chemical industries. Hence, the accidents that happened in major losses, generally occur because of the failure of a number of the system or barriers within the process safety management system. For many years, accidental releases of toxic, reactive, flammable liquids and gases, have been recorded in processes involving highly dangerous chemicals that can lead to fires, explosions or the accidental of hurricane, leak and others. The main of contributor that led to the accidents such as human error, organizational error, design error and the technical error. All the accidents occurred may lead to the damages of equipment, environment, and affect the large-scale health and welfare employees. Lack of understanding and information on the what event that can contribute to the accident may later result in future similar accidents. Research methods are split broadly into quantitative and qualitative methods in order to produces a richer and more comprehensive understanding of research area. These methods use is based on the accidents analysis data on chemical substances involved, types of hazards, operating parameter conditions, types of equipment, accident contributors and types of process. The main objective of this study is to identify the root cause in order to get to the underlying cause of the harm from the accidents occurred and describing corrective measures to prevent similar future accidents. The data or result collected were different for each types of accidents because it depends on different analysis data or underlying causes. The framework was developed based on literature review from investigation reports, journals, articles and other sources. For this study, there are 80 different types of accidents on 4 different types of industry plant that mentioned earlier chosen and identified. The guideline of identification of the hazards offers an opportunity for the redesign of the unit or equipment to remove or substantially reduce the risk, but where the risk cannot be reduced to tolerable levels by feasible redesign, in order to meet the applicable requirements, additional safety measures which need to be implemented. In these 80 accidents that were studied, the cause primarily due to equipment, human and organizational error. Based on the analysis of 80 accidents, the results show that tanks have higher possibility which is 21.51% to occur accident in process chemical plant. Most companies follow those standards and guidelines in the design, construction and operation, but tank accidents still occur. Explosion account for 43% of the accidents. There were 80 accidents, (48.33%) caused by human error which is more to organizational error 27.22% and (51.67%) caused by equipment errors which is more to technical error 27.22 %. Other causes were type of process. Most of those accidents would have been avoided if good engineering have been practiced. In conclusion, this study able to improve learning from accidents and indirectly reduce accident rates in the industry.